Ajax : creating web pages with asynchronous JavaScript and XML - Woychowsky, Edmond (Bruce Perens' Open Source series., 2006)
The Easy, Example-Based Guide to Ajax for E very Web Developer Using Ajax, you can build Web applications with the sophistication and usability of traditional desktop applications and you can do it using standards and open source software. Now, for the first time, there's an easy, example-driven guide to Ajax for every Web and open source developer, regardless of experience. Edmond Woychowsky begins with simple techniques involving only HTML and basic JavaScript. Then, one step at a time, he introduces techniques for building increasingly rich applications. Don't worry if you're not an expert on Ajax's underlying technologies; Woychowsky offers refreshers on them, from JavaScript to the XMLHttpRequest object. You'll also find multiple open source technologies and open standards throughout, ranging from Firefox to Ruby and MySQL. You'll not only learn how to write "functional" code, but also master design patterns for writing rocksolid, high-performance Ajax applications. You'll also learn how to use frameworks such as Ruby on Rails to get the job done fast . Learn how Ajax works, how it evolved, and what it's good for Understand the flow of processing in Ajax applications Build Ajax applications with XML and the XMLHttpRequest object Integrate back-end code, from PHP to C# Use XSLT and XPath, including XPath Axis Develop client-side Ajax libraries to support code reuse Streamline development with Ruby on Rails and the Ruby programming language Use the cross-browser HTML DOM to update parts of a page Discover the best Ajax Web resources, including Ajax-capable JavaScript libraries.